WATER BATH UNTUK PENGATUR SUHU BERBASIS INTERNET OF THINGS - -, Firmansyah; Sugiharto, Jarot (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
Current technological advances, namely the Internet of Things with everything related to the internet and the industrial world 4.0, can help to make human work easier. A water bath is a laboratory tool used to heat chemical liquids, soak test objects, incubate bacteria using a certain temperature using air. Locally produced water baths on the Indonesian market generally only have analog temperature controls and no features connected to cellphones, actual temperature detection, time, air level and water pumps in the bath, so sometimes workers have to use other tools. such as stopwatches, rulers, glass thermometers and dippers. The water bath can then be monitored and controlled remotely via a mobile device. The impact of this water bath will make it easier for laboratory staff to work and carry out activities in the laboratory. With this, workers no longer need to monitor and control equipment directly, implementing research that limits laboratory activities will be even more effective. Then design and build a water bath. The test results show that this water bath is able to control and monitor temperature very well by measuring, the smallest average difference is -0.1 ºC at the 30 ºC point and the largest average difference is -0.35 ºC at the 70 ºC point while the smallest error is 0.29% at a point of 70 ºC and the largest error is 0.83% at a temperature of 30 ºC.